2017
DOI: 10.1189/jlb.4a0416-209rr
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous PMN apoptosis in type 2 diabetes and the impact of periodontitis

Abstract: The purpose of this study was to test the hypothesis that peripheral blood neutrophils (PMN) exhibit delayed spontaneous apoptosis in individuals with diabetes mellitus type 2 (T2DM) and that the delay is exacerbated further among people who coexpress chronic periodontitis (CP). Seventy-three individuals were enrolled, including those with T2DM ( = 16), CP ( = 15), T2DM + CP ( = 21), and healthy volunteers ( = 21). PMN apoptosis was determined by flow cytometry using TUNEL and Annexin V assays. The activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
0
26
1
Order By: Relevance
“…Interestingly, delayed neutrophil apoptotic rates have been reported in the studies mentioned above. Diverse studies in humans and mice had demonstrated that both, a dysfunctional metabolic status like type 2 diabetes mellitus and hyperglycemia are able to decrease the rate of neutrophil apoptosis [33,68,69]. Our study do not support similar ndings in the equine species, but it must be acknowledged that only spontaneous neutrophil apoptosis was assessed, in absence of stimuli reagents.…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, delayed neutrophil apoptotic rates have been reported in the studies mentioned above. Diverse studies in humans and mice had demonstrated that both, a dysfunctional metabolic status like type 2 diabetes mellitus and hyperglycemia are able to decrease the rate of neutrophil apoptosis [33,68,69]. Our study do not support similar ndings in the equine species, but it must be acknowledged that only spontaneous neutrophil apoptosis was assessed, in absence of stimuli reagents.…”
Section: Discussioncontrasting
confidence: 89%
“…Manosudprasit et al . evaluated caspase‐3, ‐8, and ‐9 levels of peripheral blood neutrophils in patients with chronic periodontitis and type 2 Diabetes mellitus (T2DM).…”
Section: Discussionmentioning
confidence: 99%
“…Manosudprasit et al 31 evaluated caspase-3, -8, and -9 levels of peripheral blood neutrophils in patients with chronic periodontitis and type 2 Diabetes mellitus (T2DM). They reported that caspase-3 was significantly higher in T2DM patients with and without CP compared to healthy controls (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the link between oral inflammation and systemic PMN responses, we found increased priming of PMNs in the circulation 1 week after cessation of oral hygiene practices, using a human model of experimental gingivitis ( 41 ). Another study showed that the presence of PD in diabetic patients exacerbated the suppression of apoptosis of circulating PMNs compared to diabetes alone ( 195 ). Although PMNs generally are recruited across the inflamed endothelium in a highly targeted manner to respond to an acute or chronic threat, what happens when a patient has an additional underlying inflammatory complication or comorbidity?…”
Section: Pmns Are a Nexus For Simultaneously Occurring Inflammatory Tmentioning
confidence: 99%